Analysis of the intraday effects of economic releases on the currency market - Omid Rezania; Svetlozar T. Rachev; Edward Sun; Frank J. Fabozzi (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2010)
Using four years of second-by-second executed trade data, we study the intraday effects of a representative group of scheduled economic releases on three exchange rates: EUR/, JPY/ and GBP/. Using wavelets to analyze volatility behavior, we empirically show that intraday volatility clusters increase as we approach the time of the releases, and decay exponentially after the releases. Moreover, we compare our results with the results of a poll that we conducted of economists and traders. Finally, we propose a wavelet volatility estimator which is not only more efficient than a range estimator that is commonly used in empirical studies, but also captures the market dynamics as accurately as a range estimator. Our approach has practical value in high-frequency algorithmic trading, as well as electronic market making.
urn:nbn:de:swb:90-197720
Keywords: F31; G14; G15; 330; Foreign exchange; volatility estimation; economic release; wavelet; high frequency; Wechselkurs; Wirtschaftsinformation; Volatilität; Zeit; Schätzung; US-Dollar; Yen; Euro; Pfund Sterling; Welt